Загальні тенденції розвитку хлібопекарських підприємств України - Літвиненко, Олександра Олександрівна; Мерзлікіна, Юлія Миколаївна; Саєнко, Юлія Володимирівна (НТУ "ХПІ", 2018)
Досліджено загальні тенденції розвитку хлібопекарських підприємств України, проблеми і перспективи подальшого розвитку в сучасних умовах господарювання. Надано класифікацію по потужності виробництва наявних сегментів хлібопекарських підприємств. Визначено основні показники вибору споживачів хлібобулочних виробів та розкрито їх сутність. У роботі зроблено акцент щодо перспективності наявності індивідуальної упаковки хлібопекарських виробів, яка за оцінками фахівців, в Україні на сьогоднішній день складає близько половини ринку. Індивідуальна упаковка – це презентабельність, гігієнічність, транспортабельність і гарантований термін зберігання. З огляду на те, що багато вітчизняних виробників хлібопекарських виробів, для утримання займаної частки ринку, йдуть по шляху здешевлення своєї продукції за рахунок менш дорогої упаковки у роботі запропоновано розглянути доцільність та економічність упаковки флоу-пак. Зроблено висновок, що всі вимоги вибору споживачів можуть задовольнити саме приватні пекарні, роблячи свою продукцію конкурентоспроможною і цікавою споживачеві. Слідуючи тенденціям ринку безпрограшною буде позиція підприємств, зорієнтован их на стратегію свіжої випічки і постачання споживачам якісної продукції за прийнятною ціною.

The general trends in the development of bakery enterprises of Ukraine, problems and prospects for further development in the current economic conditions are investigated. Classification according to production capacity of existing segments of bakery enterprises is given. Along with traditional bakeries, many other manufacturers have appeared on the market. Today, the market of bakery products is affected by the increase in mini bakeries: among them there are those located in residential areas, as well as own production of some retail chains. Since foreign trade has little influence on this market, the nature of further processes in the bakery market in Ukraine will depend on the dynamics of domestic demand. Despite the contraction of the market in recent years, bread continues to be one of the main products in the Ukrainian diet, so the demand for it will always be present. Its level depends on purchasing power, on the number of the population of Ukraine, on the perception of consumers' lifestyle producers and on the exact creation of new product offers. The main indicators of the choice of consumers of bakery products are determined and their essence is revealed. The emphasis is placed on the prospects for the availability of individual packaging of bakery products, which, according to experts, in Ukraine today is about half of the market. Individual packaging is presentability, hygiene, transportability and guaranteed shelf life. Considering that many domestic producers of bakery products, in order to retain their market share, are on the way to reduce their prices due to less expensive packaging, it is suggested to consider the feasibility and economics of the flow-pack packaging. It is concluded that all requirements of consumers' choice can be met by private bakeries, making their products competitive and interesting to the consumer. Following the tendencies of the market, the position of enterprises oriented to the strategy of fresh baking and supplying consumers with quality products at an affordable price will be a win-win situation.
General trends of development of bread-baking enterprises of Ukraine
Keywords: хлібопекарські вироби; попит; асортимент; споживачі; упаковка; bakery products; assortment; consumers; packaging